GLYCOGEN IN HUMAN TESTICULAR BIOPSY MATERIAL PRELIMINARY REPORT - ARZAC, JOSE PEDRO (HOSPITAL Spanish, CD. MEXICO, DF, MEX, 1964)
THE study of intermediary carbohydrate metabolism is the pathway to increasing our knowledge of the metabolism of many other substances of fundamental biologic importance. It has been shown that sex hormones, among others, are able to influence such pheno
J CLIN ENDOCRINOL
Keywords: GLYCOGEN, HUMAN, TESTICULAR, BIOPSY, MATERIAL, REPORT; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA